Nanofabrication Principles, Capabilities and Limits - Cui, Zheng (Springer International Publishing : Imprint: Springer, 2017)
This second edition of Nanofabrication is one of the most comprehensive introductions on nanofabrication technologies and processes. A practical guide and reference, this book introduces readers to all of the developed technologies that are capable of making structures below 100nm. The principle of each technology is introduced and illustrated with minimum mathematics involved. Also analyzed are the capabilities of each technology in making sub-100nm structures, and the limits of preventing a technology from going further down the dimensional scale. This book provides readers with a toolkit that will help with any of their nanofabrication challenges.